Вимір характеристики спрямованості акустичного випромінювання БПЛА - Громова, С. О. (ХНУРЕ, 2021)
The characteristic of the straightness of the acoustic vibration of the UAV is one of the most important characteristics of the victorious when it is detected and identified. The factor of straightforwardness of vypromynuvannya vikoristovyvayutsya for the development of cleanliness in the noise and lightness of small UAV.
Keywords: БПЛА; акустичне випромінювання